The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009 13th International Conference Information Visualisation 2009
DOI: 10.1109/iv.2009.80
|View full text |Cite
|
Sign up to set email alerts
|

The Need for a Reconciliation Pedagogy: Educating for a More Holistic, Shared Australian Cultural Heritage

Abstract: [1,2,3,4,5]. It is through supervised role play games that we feel a more holistic shared, reconciliatory cultural heritage knowledge can be shaped. This paper concludes with some recommendations for the implementation of a more inclusive reconciliation pedagogy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Leveraging school-aged children's prior knowledge of using computer games, the reconciliation game provides a fun environment for students to explore complex concepts in a visually stimulating way. This paper expands on the background in this field reported in [13] and an earlier pilot study reported in [15].…”
Section: Introductionsupporting
confidence: 52%
“…Leveraging school-aged children's prior knowledge of using computer games, the reconciliation game provides a fun environment for students to explore complex concepts in a visually stimulating way. This paper expands on the background in this field reported in [13] and an earlier pilot study reported in [15].…”
Section: Introductionsupporting
confidence: 52%
“…However, it is the concern of the authors of this paper and others that the national curriculum is not effective in promoting reconciliation as an important part of a student's education. To this end we proposed a reconciliation pedagogy (see [10]). As a pedagogical tool in this reconciliation pedagogy a game was developed.…”
Section: Resultsmentioning
confidence: 99%
“…In order to address the gap in the curriculum for Australian contemporary history the authors of this paper proposed a new 'reconciliation pedagogy' (see [10]). Reconciliation is the process of reconciling differences, whether they be historical misrepresentations of cultural identity or any other site of dissonance.…”
Section: A Reconciliation Pedagogymentioning
confidence: 99%
“…While largely reflective of the diversity of global peoples and their unique colonial encounters, we believe important lessons for Canada can be garnered from scholars studying effective ways to enact reconciliation through education. Writing from an Australian context, scholars MacGill and Wyeld (2009) maintain: "Reconciliation is concerned with social justice and constructions of cultural identity" (p. 555). These authors assert that reconciliation not only includes issues of land dispossession but also extends to the ongoing loss of cultural identity amongst the colonized.…”
Section: Global Lessons Of Reconciliationmentioning
confidence: 99%
“…To this end, mainstream media has played a significant role in influencing young learners by presenting a biased version of history that erases the presence of the original occupants and largely ignores the violent history of the colonizers. This "whitewashed" form of media is currently being challenged by new forms of media emanating from Indigenous perspectives (MacGill & Wyeld, 2009). Lately, Wyeld (2016) has used 3-D gaming as a way to foster empathy and raise important questions from students around Indigenous issues.…”
Section: Global Lessons Of Reconciliationmentioning
confidence: 99%